Polysilsesquioxane gas separation membrane as well as preparation method and application thereof
By copolymerizing bridged silsesquioxane and pendant silsesquioxane precursor, a polysilsesquioxane gas separation membrane was prepared to form a composite film structure, which solved the problem of traditional silicon dioxide films in hydrothermal environments. The stability problem achieves efficient separation and purification of helium, reducing costs and energy consumption.
Patent Information
- Application Number
- CN202410731757.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-06
AI Technical Summary
Traditional silica films are prone to hydrolysis in hydrothermal environments, which is not conducive to industrial production and helium separation and purification.
The polysilsesquioxane gas separation membrane is prepared by copolymerizing the bridged silsesquioxane precursor and the pendant silsesquioxane precursor by sol-gel method to form a 'rigid skeleton/flexible micropore' Composite membrane structure regulates the pore size and pore environment, and improves the separation selectivity of helium and other gases.
It realizes efficient molecular sieving of helium, reduces cost and energy consumption, improves the separation selectivity of helium from nitrogen and methane, solves the stability problem of traditional methods, and is suitable for helium extraction of liquefied natural gas exhaust.
Smart Images

Figure CN119113824A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas separation materials, and in particular to a polysilsesquioxane gas separation membrane and a preparation method and application thereof. Background Art
[0002] Helium (He) is a non-renewable rare gas and an important strategic gas resource that is indispensable for the development of national defense and high technology. It plays an irreplaceable role in defense, industry, and technology fields such as aerospace, nuclear weapons, submarines, nuclear magnetic resonance, and semiconductors. However, He is mainly distributed in the mantle, rocks, air, and natural gas. The He content in the air is relatively low, making it difficult to utilize as a resource. Therefore, an important way to utilize He as a resource is to extract it from natural gas, especially to extract He from the tail gas of liquefied natural gas.
[0003] At present, the main methods for extracting helium from liquefied natural gas tail gas are cryogenic method, pressure swing adsorption method and absorption method. The development of these methods in the existing technology has been relatively mature, but there are also some problems, such as high cost, high energy consumption and low operational flexibility. However, due to He (0.26nm)
[0004] The difference in kinetic diameter between He and N2 (0.364nm) allows separation based on their molecular size. Membrane separation technology can be coupled with some traditional technologies to achieve He recovery and purification, and is considered to be the most promising solution for helium extraction from liquefied natural gas tail gas in the future. In the current prior art, there are inorganic membrane materials for He separation using silicon dioxide, but traditional silicon dioxide membranes are easily hydrolyzed in a hydrothermal environment, which is not conducive to industrial production and separation and purification of helium. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a polysilsesquioxane gas separation membrane and a preparation method and application thereof, which solves the problem in the prior art that the silicon dioxide membrane is easily hydrolyzed in a hydrothermal environment, which is not conducive to industrial production and separation and purification of helium.
[0006] The present invention solves the above technical problems by the following technical means:
[0007] In a first aspect, the present invention provides a polysilsesquioxane gas separation membrane, comprising a polysilsesquioxane layer located at the outermost layer of the gas separation membrane, wherein the raw materials for preparing the polysilsesquioxane layer include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer.
[0008] In combination with the first aspect, in some embodiments, the molar ratio of the bridging silsesquioxane monomer to the pendant silsesquioxane monomer is (5-10):(1-5).
[0009] In combination with the first aspect, in some embodiments, the bridging silsesquioxane monomer is any one of 1,2-bis(triethoxysilyl)ethane, bis(triethoxysilyl)methane, 1,3-bis(triethoxysilyl)propane, and 1,2-bis(triethoxysilyl)benzene, and the pendant silsesquioxane monomer is any one of N-(trimethoxysilylpropyl)imidazole, methyltrimethoxysilane, methyltriethoxysilane, and phenyltriethoxysilane.
[0010] In combination with the first aspect, in some embodiments, the gas separation membrane includes an α-Al 2 O 3 support, an α-Al 2 O 3 particle layer, a transition layer and a polysilsesquioxane layer formed in sequence from inside to outside.
[0011] In combination with the first aspect, in some embodiments, the transition layer is formed by drying and sintering boehmite sol and SiO2-ZrO2 sol.
[0012] In combination with the first aspect, in some embodiments, the α-Al2O3 particle layer includes α-Al2O3 particles with particle sizes of 0.2 μm and 2 μm. α-Al2O3 particles with different particle sizes can gradually reduce macropore defects and pore sizes.
[0013] In a second aspect, the present invention provides a method for preparing a polysilsesquioxane gas separation membrane, comprising the following steps:
[0014] The bridging silsesquioxane monomer and the pendant silsesquioxane monomer are dissolved in anhydrous ethanol, and a hydrochloric acid solution is added dropwise under stirring to obtain a mixed solution, and then anhydrous ethanol is added to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 0.01-10%, and then the mixture is stirred and reacted at room temperature for 10-15 hours to obtain a polysilsesquioxane sol;
[0015] Coating the α-Al2O3 particle sol on the outer surface of the α-Al2O3 support, calcining at 500-1200°C for 10-20 minutes, repeating the coating and calcining steps 3-5 times, and forming an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support;
[0016] The boehmite sol and SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer, and dried and sintered to form a transition layer;
[0017] Subsequently, polysilsesquioxane sol is coated on the transition layer, and calcined in a N2 atmosphere at 100-400° C. for 0.5-2 hours, and repeated 1-3 times to obtain a polysilsesquioxane gas separation membrane.
[0018] In combination with the second aspect, in some embodiments, the concentration of the hydrochloric acid solution is 0.1-10 mmol / g.
[0019] In combination with the second aspect, in some embodiments, the step of coating the outer surface of the α-Al2O3 support with an α-Al2O3 particle sol includes: sequentially and evenly coating the outer surface of the α-Al2O3 support with an α-Al2O3 small particle sol and an α-Al2O3 large particle sol, wherein the α-Al2O3 small particle sol is prepared by uniformly dispersing α-Al2O3 particles with a particle size of 0.2 μm in a SiO2-ZrO2 sol, and the α-Al2O3 large particle sol is prepared by uniformly dispersing α-Al2O3 particles with a particle size of 2 μm in a SiO2-ZrO2 sol.
[0020] In a third aspect, the present invention further provides the use of the polysilsesquioxane gas separation membrane of the first aspect or the polysilsesquioxane gas separation membrane prepared by the preparation method described in the second aspect in helium separation and extraction.
[0021] The polysilsesquioxane gas separation membrane of the present invention constructs a composite membrane structure with "rigid skeleton / flexible micropores" through the strategy of copolymerization of a bridged silsesquioxane precursor and a pendant silsesquioxane precursor, thereby realizing the coordinated regulation of the pore size and pore microenvironment of the separation membrane. The two precursors can be 1,2-bis(triethoxysilyl)ethane (BTESE) and N-(trimethoxysilylpropyl)imidazole (SiIm), respectively. The network structure formed by the bridged precursor BTESE is relatively loose and has a larger pore size, while the steric effect of the side chain pendant group can effectively and accurately reduce the membrane pore size, and finally form a composite membrane pore structure of "rigid skeleton / flexible micropores". The prepared polysilsesquioxane gas separation membrane can improve the separation selectivity of He / N2 and He / CH4 while maintaining the permeation flux of He.
[0022] The polysilsesquioxane gas separation membrane of the present invention achieves efficient molecular sieving of He / N2 by finely regulating the pore size and pore environment of the polysilsesquioxane network, and is very effective in extracting helium from liquefied natural gas tail gas, thereby solving the problems of high cost and high energy consumption of traditional methods, as well as the problem that traditional silica membranes have poor hydrothermal stability, making them unfavorable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the molecular structure of a bridging silsesquioxane monomer and a pendant silsesquioxane monomer;
[0024] Figure 2 Schematic diagram of the structure of "rigid skeleton / flexible micropores" formed by polysilsesquioxane gas separation membrane;
[0025] Figure 3 is a particle size distribution diagram of the polysilsesquioxane sol in Examples 1-5;
[0026] Figure 4 is the infrared spectrum of the copolymerized polysilsesquioxane gel powder in Examples 1-5;
[0027] Figure 5 TG curve diagram of the copolymerized polysilsesquioxane sol in Examples 1-5;
[0028] Figure 6 is the N2 adsorption-desorption isotherm of the polysilsesquioxane gas separation membrane in Examples 1-5;
[0029] Figure 7 The graph is a test result of the gas permeability of the polysilsesquioxane gas separation membrane in Examples 1-5 to a gas having a dynamic diameter;
[0030] Figure 8 Graph showing the results of the He / N2 separation performance test of the polysilsesquioxane gas separation membrane in Examples 1-5;
[0031] Fig. 9 This is a graph showing the results of the He / CH4 separation performance test of the polysilsesquioxane gas separation membrane in Examples 1-5. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials, equipment or instruments used, if no manufacturer is specified, are all conventional products that can be purchased on the market.
[0034] Silica is an inorganic membrane material commonly used to prepare He separation, but traditional silica membranes are easily hydrolyzed in a hydrothermal environment, which is not conducive to industrial production and separation and purification of helium. The present invention uses a sol-gel method to prepare a polysilsesquioxane gas separation membrane using α-Al2O3 as a support by copolymerizing a bridged silsesquioxane precursor with one or more pendant silsesquioxane monomer precursors, and finally forms a composite membrane pore structure of "rigid skeleton / flexible micropores". The composite membrane pore structure can be found in Figure 2As a result, N2 and CH4 molecules are retained based on the size exclusion effect in the rigid micropores, and He molecules can selectively pass through the composite membrane pore structure due to their smaller kinetic diameter. The composite membrane pore structure has high He / N2 and He / CH4 selectivity and can be well applied to the fields of helium extraction from liquefied natural gas tail gas.
[0035] The polysilsesquioxane gas separation membrane of the present invention comprises an α-Al2O3 support, an α-Al2O3 particle layer, a transition layer and a polysilsesquioxane layer which are sequentially formed from the inside to the outside, and the raw materials for preparing the polysilsesquioxane layer comprise a bridging silsesquioxane monomer and a pendant silsesquioxane monomer. The molar ratio of the bridging silsesquioxane monomer to the pendant silsesquioxane monomer is (5-10): (1-5), the bridging silsesquioxane monomer is any one of 1,2-bis(triethoxysilyl)ethane, bis(triethoxysilyl)methane, 1,3-bis(triethoxysilyl)propane and 1,2-bis(triethoxysilyl)benzene, and the pendant silsesquioxane monomer is any one of N-(trimethoxysilylpropyl)imidazole, methyltrimethoxysilane, methyltriethoxysilane and phenyltriethoxysilane. Preferably, the bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane (BTESE), and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole (SiIm). The molecular structures of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer are shown in Figure 1 The transition layer is formed by drying boehmite sol and SiO2-ZrO2 sol. The α-Al2O3 particle layer contains α-Al2O3 particles with particle sizes of 0.2 μm and 2 μm.
[0036] The preparation method of the polysilsesquioxane gas separation membrane of the present invention comprises the following steps:
[0037] The bridging silsesquioxane monomer and the pendant silsesquioxane monomer are dissolved in anhydrous ethanol, and a hydrochloric acid solution is added dropwise under stirring to obtain a mixed solution, and then anhydrous ethanol is added to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 0.01-10%, and then the mixture is stirred and reacted at room temperature for 10-15 hours to obtain a polysilsesquioxane sol;
[0038] Coating the α-Al2O3 particle sol on the outer surface of the α-Al2O3 support, calcining at 500-1200°C for 10-20 minutes, repeating the coating and calcining steps 3-5 times, and forming an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support;
[0039] The boehmite sol and SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer, and dried and sintered to form a transition layer;
[0040] Subsequently, polysilsesquioxane sol is coated on the transition layer, and calcined in a N2 atmosphere at 100-400° C. for 0.5-2 hours, and the process is repeated 1-3 times to obtain a polysilsesquioxane gas separation membrane.
[0041] The polysilsesquioxane gas separation membrane and the preparation method thereof of the present invention are described in detail below through Examples 1-7.
[0042] The preparation method of the α-Al2O3 support used in the following examples is as follows: a tubular α-Al2O3 ceramic membrane support is prepared by extrusion molding, 82wt% of α-Al2O3 with an average particle size of 6.18 microns and 5wt% of carboxymethyl cellulose, 10wt% of kaolin and 3wt% of titanium dioxide are mixed evenly under mechanical stirring, and then aged in an oven at 25°C for 12h, and a green billet is prepared by extrusion molding. The green billet is dried in an oven at 30°C for 12h, and the dried green billet is sintered in an electric furnace at a temperature of 1200-1700°C to obtain an α-Al2O3 support.
[0043] Example 1
[0044] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer in a molar ratio of 7:3, wherein the bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane, and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0045] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0046] Take the bridging silsesquioxane monomer and the pendant silsesquioxane monomer and dissolve them in anhydrous ethanol, add a hydrochloric acid solution with a concentration of 5.084 mmol / L under vigorous stirring to obtain a mixed solution, and then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 5%, and then stir the reaction at room temperature for 12 hours to obtain a clear and transparent polysilsesquioxane sol.
[0047] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol. Similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 550℃ for 15min. The coating and calcination steps are repeated 4 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0048] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0049] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 300° C. in a N 2 atmosphere for 1 hour. This process was repeated twice to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0050] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0051] Example 2
[0052] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer in a molar ratio of 9: 1. The bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane, and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0053] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0054] Take the bridging silsesquioxane monomer and the pendant silsesquioxane monomer and dissolve them in anhydrous ethanol, add a hydrochloric acid solution with a concentration of 5.084 mmol / L under vigorous stirring to obtain a mixed solution, and then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 5%, and then stir the reaction at room temperature for 12 hours to obtain a clear and transparent polysilsesquioxane sol.
[0055] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol. Similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 550℃ for 15min. The coating and calcination steps are repeated 4 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0056] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0057] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 300° C. in a N 2 atmosphere for 1 hour. This process was repeated twice to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0058] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0059] Example 3
[0060] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer in a molar ratio of 8: 2. The bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane, and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0061] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0062] Take the bridging silsesquioxane monomer and the pendant silsesquioxane monomer and dissolve them in anhydrous ethanol, add a hydrochloric acid solution with a concentration of 5.084 mmol / L under vigorous stirring to obtain a mixed solution, and then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 5%, and then stir the reaction at room temperature for 12 hours to obtain a clear and transparent polysilsesquioxane sol.
[0063] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol. Similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 550℃ for 15min. The coating and calcination steps are repeated 4 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0064] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0065] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 300° C. in a N 2 atmosphere for 1 hour. This process was repeated twice to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0066] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0067] Example 4
[0068] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include pendant silsesquioxane monomers, wherein the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0069] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0070] The pendant silsesquioxane monomer was dissolved in anhydrous ethanol, and a hydrochloric acid solution with a concentration of 5.084 mmol / g was dropped into it under vigorous stirring to obtain a mixed solution, and then anhydrous ethanol was added to adjust so that the total mass fraction of the pendant silsesquioxane monomer in the mixed solution was 5%. The mixture was then stirred and reacted at room temperature for 12 hours to obtain a clear and transparent polysilsesquioxane sol.
[0071] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol. Similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 550℃ for 15min. The coating and calcination steps are repeated 4 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0072] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0073] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 300° C. in a N 2 atmosphere for 1 hour. This process was repeated twice to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0074] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0075] Example 5
[0076] The raw material for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment includes a bridging silsesquioxane monomer, wherein the bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane.
[0077] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0078] Take a bridging silsesquioxane monomer and dissolve it in anhydrous ethanol. Add a hydrochloric acid solution with a concentration of 5.084 mmol / g under vigorous stirring to obtain a mixed solution. Then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 5%. Then, stir and react at room temperature for 12 hours to obtain a clear and transparent polysilsesquioxane sol.
[0079] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol. Similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 550℃ for 15min. The coating and calcination steps are repeated 4 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0080] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0081] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 300° C. in a N 2 atmosphere for 1 hour. This process was repeated twice to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0082] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0083] The performance of the polysilsesquioxane gas separation membranes and their intermediates prepared in Examples 1-5 was tested as follows:
[0084] (1) Particle size detection
[0085] The particle size distribution of the polysilsesquioxane sol in Examples 1-5 was characterized using a nanoparticle size analyzer. The polysilsesquioxane sol sample to be tested was ultrasonicated for 5 minutes and then placed in a sample tube to start testing. Figure 3 .
[0086] Figure 3 The particle size distribution of the polysilsesquioxane sol in Examples 1-5 is shown in FIG. 1 . In Examples 1-5, the polysilsesquioxane sol contains bridging silsesquioxane monomers and pendant silsesquioxane monomers in different molar ratios. Figure 3 The data showed that the particle size of all sols ranged from 0.7 to 10 nm, with an average particle size below 4 nm.
[0087] (2) Infrared spectroscopy analysis
[0088] The polysilsesquioxane layer powder was scraped from the surface of the polysilsesquioxane gas separation membrane prepared in Examples 1-5 as samples, and the structure of the sample powder was characterized by Fourier transform infrared spectrometer (FTIR). The specific test method is as follows: the powdered samples scraped from Examples 1-5 were fully mixed and ground with spectrally pure potassium bromide (KBr) in a mortar, and then the mixture of the sample and potassium bromide was pressed into a circular sheet using a special tableting mold for testing. The scanning range of the test wave number was 4000-400cm -1 , the number of scans is 128 times. The test results are shown in Figure 4 .
[0089] from Figure 4 It can be seen that the peak shapes of all powders are roughly the same, and all polysilsesquioxanes are observed at a wave number of 1010 cm -1 There is a strong absorption peak near 900 cm, which is formed by the symmetric stretching vibration of oxygen atoms in Si-O-Si. -1 The nearby peaks are attributed to the asymmetric stretching vibration of the oxygen atom in Si-OH. The existence of these two peaks proves that the polysilsesquioxane precursor has successfully undergone hydrolysis and polycondensation reaction; -1 There is a strong absorption peak nearby, while at the same position, there is no absorption peak in the spectrum of BTESE, and with the increase of SiIm content, the absorption peak gradually increases from nothing to something, which is caused by the vibration of the unique C=N group in the SiIm structure; at the same time, the successful doping of SiIm is verified, indicating that the BTESE-SiIm powder is a polysiloxane structure containing imidazole ring units, and further indicating that the surface of the polysilsesquioxane gas separation membrane is a polysiloxane structure containing imidazole ring units.
[0090] (3) Thermal stability analysis
[0091] The polysilsesquioxane sol prepared in Example 1-5 was used as a sample, and the thermal stability of the polysilsesquioxane sol was tested by a thermogravimetric analyzer to further confirm the temperature used for preparing the film. The polysilsesquioxane sol sample was dried in an oven at 120°C for 4 hours to remove the physically adsorbed water and anhydrous ethanol in the sample, and then tested by a thermogravimetric analyzer. The test atmosphere was N2, the temperature range was 40-800°C, and the heating rate was 10°C / min. The test results are shown in Figure 5 .
[0092] from Figure 5It can be seen that BTESE has good thermal stability, and the overall weight loss is divided into two stages. The first stage is 200℃-400℃. This stage is mainly due to the presence of some unhydrolyzed condensed groups in the material, and the temperature rises to further react. The second stage is 400℃-700℃, mainly due to the decomposition of organic groups such as carbon. The overall weight loss of SiIm is divided into three stages. The first stage is 150℃-250℃. This stage is mainly due to the presence of some unhydrolyzed condensed groups in the material, and the temperature rises to further react. The second stage is 250℃-400℃, mainly due to the cleavage of the imidazole ring. The third stage is 400℃-700℃, mainly due to the decomposition of organic groups such as carbon. The starting temperature of thermal decomposition of BTESE-SiIm is between the two, closer to BTESE, so the coating temperature and calcination temperature are determined to be 100-400℃.
[0093] (4) Specific surface area detection
[0094] The polysilsesquioxane gas separation membrane prepared in Example 1-5 was used as a test sample, and the adsorption / desorption isotherm of N2 (77K) was measured by a specific surface adsorption instrument to determine the specific surface area and pore volume of the material. Before the gas adsorption test, the sample to be tested was placed in a vacuum condition at 120°C for degassing and activation for 10 hours. The vacuum degree of the polysilsesquioxane gas separation membrane was tested by a fully automatic true density tester at 40°C with He as a probe. The test results are shown in Figure 6 and Table 1.
[0095] Table 1
[0096] <![CDATA[Specific surface area S BET (m 2 / g)]]> <![CDATA[Pore volume V total (cm 3 / g)]]> <![CDATA[True density (g / cm 3 )]]> BTESE 729 0.49 1.6095 BS-9:1 438 0.36 1.5922 BS-8:2 158 0.11 1.5574 BS-7:3 0 0.05 1.5193 SiIm 0 0.099 -
[0097] from Figure 6It can be seen from the data that BTESE, BS-9:1 and BS-8:2 are typical type I adsorption isotherms, proving that these materials are all microporous materials with rigid pores. The N2 adsorption of SiIm and BS-7:3 samples is almost zero, indicating that these two materials are "non-porous" structures. It is speculated that the imidazole ring groups of SiIm occupy the pores in the rigid Si-O-Si network, resulting in blockage of the pores in the matrix, thereby forming a relatively dense structure, that is, a composite structure of "rigid skeleton / flexible micropores". It can be seen from the data in Table 1 that the pore volume and specific surface area of the gas separation membrane containing BTESE-SiIm copolymer are smaller than those of the gas separation membrane prepared by pure BTESE, and as the proportion of SiIm increases, the pore volume and specific surface area gradually decrease, thereby verifying the above speculation: some side chain groups in the SiIm structure are stacked and filled in the formed network, reducing the effective pore size of the pores. When the ratio of BTESE to SiIm is 7:3, the specific surface area drops to zero, indicating that as the ratio of SiIm precursor increases, the organic side chains obviously occupy the gaps in the rigid Si-O-Si network, and the network tends to be more and more dense. This proves that the copolymerization of BTESE and SiIm can effectively regulate the network structure.
[0098] (5) Gas permeability test
[0099] The gas permeation separation performance of the polysilsesquioxane gas separation membrane prepared in Examples 1-5 was evaluated using a gas permeation separation device built in the laboratory. The temperature range of the single gas permeation test was 40-200°C, and the tested gases were a series of gases with dynamic diameters: He (0.26nm), H2 (0.289nm), CO2 (0.33nm), N2 (0.364nm), and CH4 (0.38nm). By adjusting the back pressure valve, the inlet side of the tubular membrane was kept at a certain pressure, and the pressure difference between the feed and the permeation test was kept at about 0.2MPa, and the gas permeation was promoted by the pressure difference. Before the test, the polysilsesquioxane gas separation membrane was installed in the membrane assembly for pretreatment, and the membrane was heated to 200°C, and He was purged with a flow rate of 50ml / min for at least 6h, the purpose of which was to remove water molecules adsorbed on the membrane surface and inside the membrane. When the temperature of the membrane and the pressure difference between the inside and outside of the membrane reached a stable state, the permeation test was started.
[0100] The gas permeability and ideal selectivity are calculated as follows:
[0101] P i =F i / AΔP i
[0102] α ij =P i / P j
[0103] Where P i and P j (mol / (m 2 ·s·Pa)) are the permeability of gas components i and j, respectively, F i (mol / s) is the molar flow rate of component i through the membrane, and the volume flow rate of gas through the membrane is measured by an electronic soap film flowmeter. A (m 2 ) is the effective area of the membrane, ΔP i (Pa) is the pressure difference between component i on both sides of the membrane, a ij is the ideal selection coefficient of component i for j. The test results are shown in Figure 7 , where a is the single gas permeability performance diagram of the membrane, and b is the relationship diagram between the dimensionless gas permeability and the dynamic diameter of the membrane.
[0104] from Figure 7 It can be seen that the polysilsesquioxane gas separation membranes prepared in Examples 1-5 have different permeation fluxes for gas molecules of different sizes, and the larger the gas dynamic diameter, the smaller the permeation flux. This shows that BTESE, BTESE-SiIm, and SiIm membranes have a size screening effect on the separation of gas molecules of different dynamic diameters. Among all membranes, BTESE has a higher gas permeation flux, which is determined by its rigid porosity. With the increase of SiIm content, the permeation flux of BTESE-SiIm membrane to various gases decreases, which is the same as the result of the decrease in specific surface area and pore volume of the corresponding gas separation membrane, proving that as the proportion of SiIm in the precursor increases, the structure of the membrane will become more and more dense, and it will tend to be a non-porous structure in appearance.
[0105] (6) Separation performance test of He / N2 mixed gas
[0106] The polysilsesquioxane gas separation membranes prepared in Examples 1-5 were used as sample membranes to test their separation performance for He / N2 and He / CH4 mixed gases. Figure 8 and Fig. 9 .
[0107] from Figure 8It can be seen that as the proportion of SiIm in the membrane structure increases, the permeability of the prepared polysilsesquioxane separation membrane decreases, while the He / N2 and He / CH4 selectivities show a trend of first increasing and then decreasing. It is speculated that when the SiIm content is low, its side chains fill the pores formed by Si-O-Si, hindering the passage of large molecules, but at the same time, there is a certain activity space (free volume) in the side chains that is conducive to the permeation of small molecules. Therefore, the He selectivity is improved. When the SiIm content is high, the side chain density increases, the movement of the chain segments is restricted, and the corresponding free volume decreases. The permeation of both large and small molecules is hindered, so the selectivity decreases. From Figure 8 It can be seen that the ideal separation coefficient of BS-8:2 membrane for He / N2 is above 300, and the ideal separation coefficient for He / CH4 is above 240, which is the highest among all membranes and much higher than the corresponding Knudsen diffusion coefficient. It is speculated that the two precursors are hydrolyzed and condensed into a uniform and stable network structure, so that the prepared copolymerized polysilsesquioxane gas separation membrane has a relatively uniform and suitable effective pore size, so that molecular sieving can be effectively used to achieve the separation of He / N2 and He / CH4.
[0108] Based on the above test results, it can be seen that the polysilsesquioxane separation membrane prepared by the present invention has a good separation and purification effect on helium and can be used in the separation and purification of helium.
[0109] Example 6
[0110] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer in a molar ratio of 10:5, wherein the bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane, and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0111] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0112] Take a bridging silsesquioxane monomer and a pendant silsesquioxane monomer and dissolve them in anhydrous ethanol, add a hydrochloric acid solution with a concentration of 10.0 mmol / L under vigorous stirring to obtain a mixed solution, and then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 0.01%, and then stir and react at room temperature for 10 hours to obtain a clear and transparent polysilsesquioxane sol.
[0113] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol, and similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 500℃ for 10min, and the coating and calcination steps are repeated 3 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0114] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0115] Subsequently, 0.05 wt % polysilsesquioxane sol was coated on the transition layer and calcined in a N2 atmosphere at 100° C. for 0.5 hour. This process was repeated once to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0116] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0117] Example 7
[0118] The raw materials for preparing the polysilsesquioxane layer in the polysilsesquioxane gas separation membrane of this embodiment include a bridging silsesquioxane monomer and a pendant silsesquioxane monomer in a molar ratio of 5: 1. The bridging silsesquioxane monomer is 1,2-bis(triethoxysilyl)ethane, and the pendant silsesquioxane monomer is N-(trimethoxysilylpropyl)imidazole.
[0119] The preparation method of the polysilsesquioxane gas separation membrane of this embodiment is as follows:
[0120] Take a bridging silsesquioxane monomer and a pendant silsesquioxane monomer and dissolve them in anhydrous ethanol, add a hydrochloric acid solution with a concentration of 0.1 mmol / L under vigorous stirring to obtain a mixed solution, and then add anhydrous ethanol to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 10%, and then stir the reaction at room temperature for 15 hours to obtain a clear and transparent polysilsesquioxane sol.
[0121] Using α-Al2O3 support as base membrane, 0.2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 small particle sol, and similarly, 2μm α-Al2O3 particles are dispersed in SiO2-ZrO2 sol to obtain α-Al2O3 large particle sol. The outer surface of the α-Al2O3 support is uniformly coated with α-Al2O3 small particle sol and α-Al2O3 large particle sol in sequence, and then calcined at 1200℃ for 20min, and the coating and calcination steps are repeated 5 times to form an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support, covering all the large pores on the surface of the α-Al2O3 support, and avoiding pinholes on the separation membrane.
[0122] The boehmite sol and the SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer in sequence and dried to form a transition layer, further reducing the average pore size on the surface of the α-Al2O3 support to about 1 nm.
[0123] Subsequently, 5 wt % polysilsesquioxane sol was coated on the transition layer and calcined at 400° C. in a N 2 atmosphere for 2 hours. This process was repeated three times to obtain a polysilsesquioxane gas separation membrane with a smooth, uniform surface and no defects.
[0124] In this embodiment, the mass fraction of SiO2 in the SiO2-ZrO2 sol is 2%, the mass fraction of ZrO2 is 20%, and the mass fraction of boehmite in the boehmite sol is 5%.
[0125] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A polysilsesquioxane gas separation membrane, characterized in that: The invention comprises a polysilsesquioxane layer located at the outermost layer of the gas separation membrane, and the raw materials for preparing the polysilsesquioxane layer comprise a bridging type silsesquioxane monomer and a pendant type silsesquioxane monomer.
2. The polysilsesquioxane gas separation membrane according to claim 1, characterized in that: The molar ratio of the bridged silsesquioxane monomer to the pendant silsesquioxane monomer is (5-10): (1-5).
3. The polysilsesquioxane gas separation membrane according to claim 2, characterized in that: The bridging silsesquioxane monomer is any one of 1,2-bis(triethoxysilyl)ethane, bis(triethoxysilyl)methane, 1,3-bis(triethoxysilyl)propane, and 1,2-bis(triethoxysilyl)benzene; the pendant silsesquioxane monomer is any one of N-(trimethoxysilylpropyl)imidazole, methyltrimethoxysilane, methyltriethoxysilane, and phenyltriethoxysilane.
4. The polysilsesquioxane gas separation membrane according to any one of claims 1 to 3, characterized in that: The gas separation membrane comprises an α-Al2O3 support body, an α-Al2O3 particle layer, a transition layer and a polysilsesquioxane layer which are sequentially formed from the inside to the outside.
5. The polysilsesquioxane gas separation membrane according to claim 4, characterized in that: The transition layer is formed by drying and sintering boehmite sol and SiO2-ZrO2 sol.
6. The polysilsesquioxane gas separation membrane according to claim 5, characterized in that: The α-Al 2 O 3 particle layer contains α-Al 2 O 3 particles with particle sizes of 0.2 μm and 2 μm.
7. A method for preparing a polysilsesquioxane gas separation membrane, characterized in that: The steps include: The bridging silsesquioxane monomer and the pendant silsesquioxane monomer are dissolved in anhydrous ethanol, and a hydrochloric acid solution is added dropwise under stirring to obtain a mixed solution, and then anhydrous ethanol is added to adjust so that the total mass fraction of the bridging silsesquioxane monomer and the pendant silsesquioxane monomer in the mixed solution is 0.01-10%, and then the mixture is stirred and reacted at room temperature for 10-15 hours to obtain a polysilsesquioxane sol; Coating the α-Al2O3 particle sol on the outer surface of the α-Al2O3 support, calcining at 500-1200°C for 10-20 minutes, repeating the coating and calcining steps 3-5 times, and forming an α-Al2O3 particle layer on the outer surface of the α-Al2O3 support; The boehmite sol and SiO2-ZrO2 sol are uniformly coated on the α-Al2O3 particle layer, and dried and sintered to form a transition layer; Subsequently, polysilsesquioxane sol is coated on the transition layer, and calcined in a N2 atmosphere at 100-400° C. for 0.5-2 hours, and repeated 1-3 times to obtain a polysilsesquioxane gas separation membrane.
8. The method for preparing a polysilsesquioxane gas separation membrane according to claim 7, characterized in that: The concentration of the hydrochloric acid solution is 0.1-10 mmol / g.
9. The method for preparing a polysilsesquioxane gas separation membrane according to claim 7, characterized in that: The step of coating the outer surface of the α-Al2O3 support with α-Al2O3 particle sol comprises: uniformly coating the outer surface of the α-Al2O3 support with small α-Al2O3 particle sol and large α-Al2O3 particle sol in sequence; the small α-Al2O3 particle sol is prepared by uniformly dispersing α-Al2O3 particles with a particle size of 0.2 μm in SiO2-ZrO2 sol, and the large α-Al2O3 particle sol is prepared by uniformly dispersing α-Al2O3 particles with a particle size of 2 μm in SiO2-ZrO2 sol.
10. Use of the polysilsesquioxane gas separation membrane according to any one of claims 1 to 5 or the polysilsesquioxane gas separation membrane prepared by the preparation method according to any one of claims 6 to 9 in helium separation and extraction.
Citation Information
Patent Citations
Phenyl decorated organic-inorganic hybridization millipore silicon dioxide film preparation method
CN102218270A
Ceramic separation membrane structure and method for producing same
CN105073236A
Organic-inorganic hybrid SiO<2> membrane with CO<2> preferable permeation function and method for preparing organic-inorganic hybrid SiO<2> membrane
CN105148753A
Solvent-resistant bridged polysilsesquioxane nanofiltration composite membrane and preparation method thereof
CN111603950A
Silicon dioxide composite film with disilane precursor as well as preparation method and application of silicon dioxide composite film
CN112844064A
